Analysis and design of the portal of webquests in Portuguese language - Bottentuit Junior, João Batista (2009)
In this paper we present the whole process of analysis and implementation of an educational portal on WebQuests in Portuguese Language. The idealized portal was designed for schools and teachers, and was supposed to be a forum of sharing knowledge among Portuguese-speaking countries, thus, contributing for the dissemination to the community of the WebQuests that all Portuguese and Brazilian authors developed and used with their students. We show the stages of development and the layout of the portal, and some preliminary results obtained from a sample of environmental users.